Costo de producción y rentabilidad del cultivo de café (Coffea canephora) en la Provincia de Sucumbíos. - Argote Apolinario, Greta Esther (2013)
The study was conducted in the cantons: Cuyabeno, Putumayo, Cascales, Shushufindi and Lago Agrio province of Sucumbios, the objective was to establish economic inputs in the establishment phase and determine production costs and profitability of growing coffee. The results were obtained through surveys of 60 producers. Considered direct and indirect costs for the analysis, revenues and profitability. The coffee cultivation, down from plants obtained from nurseries and labor familiar. To prepare the ground, perform cleanings and condition areas for this crop, only two people respondents Lago Agrio Canton renewal made the coffee. In this canton used herbicides for weed control in other cantons respondents they prefer periodic manual controls the same depending on the regrowth of weeds. For the establishment of coffee, Lago Agrio Canton scored a $ 190, for weed control costing $ 136, for planting, canton Shushufindi with a $ 809, the use of fertilizers for Cuyabeno and Shushufindi cantons cost $ 168. The average direct costs of the five cantons were $1110.2 that indicates the total cost for establishing plantation range from $ 1,244 to $ 990 per hectare. The population density of planting the province of Sucumbios is 3 x 3 m, which determines 1111 plants / ha. The five cantons perform work of pruning, the burden of unproductive branches performed, only in the cantons of Shushufindi and Lago Agrio. They also perform manual control to avoid immediate weed populations. Three farmers have turned the analysis soil, with regard to fertilization and weed control five cantons apply complete fertilizer and urea. The establishment cost of coffee in five cantons ranges from $ 1,244 to $ 990, while the maintenance cost is $ 826 to $ 258. The harvest is done by practicing pepiteo consisting collect ripe fruits and improves the quality of harvested coffee. The Lago Agrio Canton scored high production of 240 qq/ ha / year, selling to middlemen. The price varies for the five cantons of $ 12 to $ 13 with an average income of $ 2,255.6 , the rate of return for the five cantons varies from 63.1 % to 22.5% , with a gross margin of $ 1,148 and $ 310 benefit / cost ratio from 1.7 to 1.2. Farmers are encouraged to implement production accounting records to determine financial parameters, to provide fast and timely credit, make foliar and soil shows every 2 years and rehabilitate coffee through maintenance pruning.